Cocrystal Formation via Resorcinol-Urea Interactions: Naringenin and Carbamazepine - Lee, Cheongcheon; Cho, A. Young; Yoon, Woojin; Yun, Hoseop; Kang, Jeong Won; Lee, Jonghwi (Crystal Growth and Design, 2019)
Improving the stability, bioavailability, and processability of active pharmaceutical ingredients (APIs) has been the key research goal in the field of pharmaceutical crystallization. Cocrystallization has been considered as an effective route to achieve this goal, and intense research over decades has revealed cocrystals of many APIs. However, most cocrystal formers have been designed based primarily on their molecular interactions not their health benefits. Herein, we choose naringenin (N), a natural flavonoid, as a novel cocrystal former as it has many health efficacies and the ability to form specific interactions. At a 1:1 stoichiometric ratio, N successfully forms a cocrystal with carbamazepine (CBZ), whose plasma concentration is known to be improved by natural flavonoids such as N. The resorcinol functional group of N and the urea functional group of CBZ are connected through hydrogen bonds, and the improved stability of the cocrystal seems to originate from this structure. The melting temperature of the cocrystal is 262 °C, which is higher than those of CBZ and N, and the better stability of the cocrystal is further confirmed by the observation of enhanced hydration stability (up to 30 days at 93% RH). This novel strategy of cocrystallization using natural flavonoids could improve the commercialization potential of API cocrystals.
Keywords: Active pharmaceutical ingredients; Co-crystal formation; Cocrystallization; Pharmaceutical crystallizations; Plasma concentration; Specific interaction; Stoichiometric ratio; Urea functional groups